KONTRIBUSI HAKIM DALAM MENEKAN TINGGINYA ANGKA PERCERAIAN MASA PANDEMI COVID-19 - Asyraful Rijal Safruddin Rijal; Zulfahmi Alwi; Muhammad Fajri (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2023)
The Covid-19 pandemic has caused problems for domestic life that have an economic impact or a livelihood, resulting in a husband and wife having continuous disagreements until they can no longer reconcile and then file for divorce at the Maros Religious Court. Divorce results and consequences continue, being one of the highest parties in the Maros Religious Court during the Covid-19 pandemic. This is what encourages judges to play the role of case breaker to reduce divorce rates as a result of decisions and leave one of the consequences of economic factors at the Maros Religious Court. This type of research is a qualitative research using an empirical juridical approach located at the Maros Religious Court, Maros Regency. Sources of data in this study are primary and secondary data sources, primary data are sources of data obtained directly from the field through interviews and documentation. Secondary data is data that does not directly collect data/research through other people or documents. Data collection methods used are interviews and documentation. Data management techniques with data reduction, data presentation and data levers. Testing the validity of the data using source triangulation, technical triangulation and time triangulation. The results of the study indicate that the factors that cause divorce in the Maros Religious Court are risk factors and are continuous, leaving one party behind and economic factors. The Role and Efforts of Judges in Suppressing Divorce Rates at the Maros Religious Court by means of reconciliation or mediation as regulated in PERMA No. 1 of 2016. The role and efforts of the judge always provide advice to married couples, this effort can also provide benefits to both. The implications of this research are expected for the Maros Religious Court to add mediation judges to avoid divorce cases. I hope that this research can provide an understanding to the readers, especially the Maros people. And the researcher hopes that in the future the Maros Religious Court can give directions so that he understands that starting a family is not a small thing, but it takes calm and great responsibility so that the household becomes sakinah mawaddah warahmah. Keywords:Contibution,Judge,and Reducing the High Divorce Rate